Efeito do lisinopril sobre parametros cardiacos e mortalidade no infarto experimental em ratos - Zornoff, Leonardo Antonio Mamede [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Tucci, Paulo J. F. [UNESP]; Spadaro, Joel [UNESP] (My University, 1997)
Purpose: To analyse the effect of early (<24 h) administration of lisinopril on ventricular remodeling and mortality after myocardial infarction (MI) in rats. Methods: Wistar rats weighing 200-250 g were submitted to ligation of the left coronary artery (LCA) and divided into three groups: SHAM (S, n = 9); infarcted and lisinopril (20 mg/kg/day) treated rats (L, n = 38); infarcted and non-treated animals (NT, n = 24). Three months later, the cardiac function was studied in isolated heart preparation according to the Langendorff technique. Starling curves were constructed using fluid injection in the left ventricular balloon, which permitted to alter the diastolic pressure range from 0 to 30 mmHg by means of pressure increments of 5 mmHg. Body weight (BW), right ventricular weight (RVW), and RVW/BW were also determined. Results: Three months after the surgery, the comparative mortality rate among groups was: S = 0; L = 34.4% and NT = 54.4% (p > 0.05, for L vs NT). In infarctions < 40% of the left ventricle (LV), the RVW/BW relation was S = L < NT (p < 0.05); the left ventricular systolic pressure was S > L > NT (p < 0.05). In infarctions > 40% of LV, the RVW/BW relation was S < L = NT (p < 0.05). For the Starling curves, the results were S > L > NT (p < 0.05). Conclusion: In our model lisinopril did not interfere with post-infarction mortality of rats, although decreasing the mortality risk in 49%, in the treated group. The drug also altered the remodeling process, preventing hypertrophy and systolic dysfunction after MI, mainly in infarctions < 40% of LV.
Effect of lisinopril on cardiac parameters and mortality after myocardial infarction in rats
Keywords: lisinopril; myocardial infarction; rat; dipeptidyl carboxypeptidase inhibitor; animal experiment; animal model; blood pressure; controlled study; drug effect; heart infarction; heart ventricle remodeling; mortality; nonhuman; analysis of variance; animal; body weight; cardiomegaly; heart contraction; heart left ventricle function; male; nonparametric test; organ size; Wistar rat; Analysis of Variance; Angiotensin-Converting Enzyme Inhibitors; Animals; Blood Pressure; Body Weight; Cardiomegaly; Lisinopril; Male; Myocardial Contraction; Myocardial Infarction; Organ Size; Rats; Rats, Wistar; Statistics, Nonparametric; Ventricular Function, Left